2014
DOI: 10.1111/cjag.12045
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ontario's Greenbelt on the Price of Vacant Farmland

Abstract: A hedonic property regression estimates a difference‐in‐differences coefficient to assess the effect of Ontario's Greenbelt zoning on vacant farmland prices around the Greater Toronto Area. In our analysis on over five hundred property sales between 2002 and 2009 we find some evidence that the Greenbelt legislation negatively influenced vacant farmland values located in close proximity to urban areas. However, the statistical significance of this result is sensitive to the exclusion of smaller parcels and to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
1
5
0
3
Order By: Relevance
“…For example, Lynch, 2001 andLynch et al, 2007, provided evidence of reduced land values of preserved parcels in Maryland. A similar result was found in the close proximity of Toronto by Deaton and Vyn, 2015. This recent evidence contrasts with that from Henneberry and Barrows, 1990, who found both negative and positive effects of agricultural zoning on farmland prices.…”
Section: The Value Of Public Policiessupporting
confidence: 54%
“…For example, Lynch, 2001 andLynch et al, 2007, provided evidence of reduced land values of preserved parcels in Maryland. A similar result was found in the close proximity of Toronto by Deaton and Vyn, 2015. This recent evidence contrasts with that from Henneberry and Barrows, 1990, who found both negative and positive effects of agricultural zoning on farmland prices.…”
Section: The Value Of Public Policiessupporting
confidence: 54%
“…Third, the sales data include properties within Ontario's Greenbelt, a land‐use policy implemented in 2004 that prohibited development of farmland around the Greater Toronto Area. This policy was found to impact farmland values in areas of the Greenbelt within 10 km of the GTA (Deaton & Vyn, 2010, 2015). To avoid potential bias from these impacts, sales of farm properties that are within the Greenbelt and within 10 km of the GTA are excluded from the data set.…”
Section: Methods and Datamentioning
confidence: 99%
“…The data set includes properties that may be affected by Ontario's Greenbelt, which was implemented in 2004 to protect farmland and environmentally sensitive land from urban development around the Greater Toronto Area (GTA). Deaton and Vyn (2010, 2015) found that the value of farm properties in the Greenbelt within 10 km of the GTA were negatively impacted. To avoid potential bias from these impacts, as well as to avoid the inclusion of properties that are less likely to have been sold for agricultural purposes, sales within 10 km of the GTA are excluded from the analysis.…”
Section: Datamentioning
confidence: 99%
“…Studies on farmland values have explored the impacts of a variety of policies. A prominent topic in the literature has been the impacts that land use regulations, such as farmland preservation policies, have on farmland values (Lynch, Gray, and Geoghegan 2007; Deaton and Vyn 2010; Liu and Lynch 2011; Deaton and Vyn 2015; Eagle et al 2015). While these policies tend to have direct impacts on farmland values, there are other types of policies for which impacts on farmland values occur indirectly.…”
mentioning
confidence: 99%